Design and optimization of an UWB microstrip patch antenna using dielectric substrates Duroid 5880 And FR4 - Chowdhury, Nusrat Tasnufa; Chowdhury, Dilruba (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electronics and Communication Engineering, 2014.